Injectable and Tunable Gelatin Hydrogels Enhance Stem Cell Retention and Improve Cutaneous Wound Healing - Dong, Yixiao; A, Sigen; Rodrigues, Melanie; Li, Xiaolin; Kwon, Sun H.; Kosaric, Nina; Khong, Sacha; Gao, Yongsheng; Wang, Wenxin; Gurtner, Geoffrey C. (Advanced functional materials, 2017)
Stem cells have shown substantial promise for various diseases in preclinical and clinical trials. However, low cell engraftment rates significantly limit the clinical translation of stem cell therapeutics. Numerous injectable hydrogels have been developed to enhance cell retention. Yet, the design of an ideal material with tunable properties that can mimic different tissue niches and regulate stem cell behaviors remains an unfulfilled promise. Here, an injectable poly(ethylene glycol) (PEG)–gelatin hydrogel is designed with highly tunable properties, from a multifunctional PEG‐based hyperbranched polymer and a commercially available thiolated gelatin. Spontaneous gelation occurs within about 2 min under the physiological condition. Murine adipose‐derived stem cells (ASCs) can be easily encapsulated into the hydrogel, which supports ASC growth and maintains their stemness. The hydrogel mechanical properties, biodegradability, and cellular responses can be finely controlled by changing hydrogel formulation and cell seeding densities. An animal study shows that the in situ formed hydrogel significantly improves cell retention, enhances angiogenesis, and accelerates wound closure using a murine wound healing model. These data suggest that injectable PEG–gelatin hydrogel can be used for regulating stem cell behaviors in 3D culture, delivering cells for wound healing and other tissue regeneration applications. An injectable poly(ethylene glycol) (PEG)–gelatin hydrogel is designed from a multifunctional PEG‐based hyperbranched polymer and a commercially available thiolated gelatin. Spontaneous gelation occurs within 2 min under the physiological condition, with finely controlled hydrogel properties. The in situ formed hydrogel significantly improves cell retention, enhances angiogenesis, and accelerates wound closure in a murine wound model.